Comparative Transcriptome and Microscopy Analyses Provide Insights into Flat Shape Formation in Peach (Prunus persica) - Guo, Jian; Cao, Ke; Li, Yong; Yao, Jia-Long; Deng, Cecilia; Wang, Qi; Zhu, Gengrui; Fang, Weichao; Chen, Changwen; Wang, Xinwei; Guan, Liping; Ding, Tiyu; et al. (Frontiers in Plant Science, 2018)
Fruit shape is an important external characteristic that consumers use to select preferred fruit cultivars. In peach, the flat fruit cultivars have become more and more popular worldwide. Genetic markers closely linking to the flat fruit trait have been identified and are useful for marker-assisted breeding. However, the cellular and genetic mechanisms underpinning flat fruit formation are still poorly understood. In this study, we have revealed the differences in fruit cell number, cell size, and in gene expression pattern between the traditional round fruit and modern flat fruit cultivars. Flat peach cultivars possessed significantly lower number of cells in the vertical axis because cell division in the vertical direction stopped early in the flat fruit cultivars at 15 DAFB (day after full bloom) than in round fruit cultivars at 35 DAFB. This resulted in the reduction in vertical development in the flat fruit. Significant linear relationship was observed between fruit vertical diameter and cell number in vertical axis for the four examined peach cultivars (R2 = 0.9964) at maturation stage, and was also observed between fruit vertical diameter and fruit weight (R2 = 0.9605), which indicated that cell number in vertical direction contributed to the flat shape formation. Furthermore, in RNA-seq analysis, 4165 differentially expressed genes (DEGs) were detected by comparing RNA-seq data between flat and round peach cultivars at different fruit development stages. In contrast to previous studies, we discovered 28 candidate genes potentially responsible for the flat shape formation, including 19 located in the mapping site and 9 downstream genes. Our study indicates that flat and round fruit shape in peach is primarily determined by the regulation of cell production in the vertical direction during early fruit development.